Evaluasi Rancangan UI/UX SIAKAD STMIK Rosma dengan Metode User Experience Questionnaire (UEQ) - Yudiana, Yudiana; Gita, Eilinafta; Darmansyah, Darmansyah; B.K, Felicia A. Stevanie` (LPPM STMIK Rosma, 2025)
SIAKAD (Academic Information System) is a technology-based information platform used by educational institutions to manage various aspects of academic administration in an integrated manner. Rosma Academic Information System (SIAKAD) is a web-based academic information system used to manage academic administration at STMIK Rosma Karawang in an efficient and structured manner. The research process began by identifying weaknesses in the existing website design through observations and interviews with active users. Designing the SIAKAD Rosma Karawang Website Design is a study that aims to improve the quality of the Rosma Karawang Academic Information System (SIAKAD) website. This research uses the User Experience Questionnaire (UEQ) method with six measurement scales and cooperative evaluation methods to identify user problems. The process began with surveys and interviews, followed by redesign and testing of the prototype using UEQ. Based on the data and calculation results in this research, it is shown that the SIAKAD Rosma Karawang UI/UX plan has succeeded in providing a good user experience, in accordance with the hedonic and pragmatic aspects evaluated, and can be recommended with a positive evaluation value (Above Average) . Keywords: Website Redesign, SIAKAD, UEQ, User Experience, Web Design.